Challenges and strategies for maintaining nutrition services in the Democratic Republic of Congo during COVID-19: a qualitative study - Bosonkie, Marc; Kazenza, Benito; Ndejjo, Rawlance; Muyer, Marie-Claire; Mafuta, Eric; Mbuyi, Ruphin; Mbunga, Branly; Lusamba, Paul-Samsom; Fawole, Olufunmilayo I.; Mapatano, Mala Ali (Frontiers in Health Services, 2025)
BackgroundThe rapid spread of COVID-19 forced governments to urgently implement non-pharmaceutical measures to stop the surge. These restrictions disrupted the provision of nutrition services. This study identified challenges faced by nutrition services using the six components of the health system and preventive strategies that can strengthen nutrition interventions during future outbreaks.MethodsA multiple-case qualitative study was carried out. Purposive sampling was used for recruitment of participants. 57 key informants were selected based on their role in the Nutrition sector at different levels of the health pyramid. The interview guide incorporated nutrition leadership, financing, workforce, infrastructure and commodities, service delivery and information system. Each topic had subtopics on challenges and adaptations. All transcripts were exported to Atlas Ti v22, and thematic analysis was conducted.ResultsInitially excluded from the national COVID-19 response, nutrition services were later integrated through advocacy by the National Nutrition Program. Despite limited funding, the government maintained support, and health workers adapted with flexible staffing approaches. Commodity shortages, including Ready-to-Use Therapeutic Food, led to the use of locally produced substitutes. Movement restrictions and fear of infection disrupted essential services such as growth monitoring and immunization. To sustain access, mitigation strategies were implemented, including tailored education, modified weighing methods, and decentralized care. Key innovations included rapid registration with anthropometric protocols, additional service points for child health activities, double-weighing scales to reduce contact, crowd control during Growth Monitoring Promotion, community-based service delivery, and improved digital integration.ConclusionsCOVID-19 disrupted all pillars of nutrition services in the DRC but also spurred innovation. Institutionalizing adaptive strategies, securing sustainable funding, and supporting local Ready-to-Use Therapeutic Food production are essential to strengthen resilience and ensure continuity of nutrition services in future health emergencies.